Various Positions : HISK 2021. - Cook, Paula; Meert, Michael (Gent : HISK, 2021)
Boutsen, Dries ; Cloostermans, Nelleke ; Cherca, Dani ; Hernaiz, Olivia ; Koplimets, Karel ; Langa, Nokukhanya ; Leenhardt, Gaelle ; Morgante, Sandrine ; Ngamba, Hadassa ; Pinto, Elisa ; Sliaupa, Paulius
Various Positions, Gosset Site, Brussel, 9 december - 30 januari 2022
boek